Antimicrobial photodynamic therapy associated with bone regeneration for peri-implantitis treatment: A case report - Garcia de Carvalho, Gabriel [UNESP] (2020)
Antimicrobial photodynamic therapy (aPDT) has emerged as a promising alternative to promote bacterial elimination and crestal bone remodeling in patients affected by peri-implantitis, once it is able to access the implant microstructure at the most restricted sites with no damage to implant surface. This paper reports a 6-month follow-up of a patient with peri-implantitis treated by surgical approach with adjunct photodynamic therapy associated to guided bone regeneration. A full thickness open-flap was performed to allow directly mechanical debridement, followed by aPDT using methylene blue 200 μg/mL under red laser irradiation (660 nm, 100 mW, 9 J), providing decontamination of implant surface and surrounding tissue. Photosensitizer was washed twice with saline solution previously to guided bone regeneration, which was carried out using xenogeneic bone and resorbable collagen membrane. After 6-month follow-up, the use of aPDT as an adjunct therapy to the surgical treatment of peri-implantitis promoted sufficient decontamination, clear evidence of bone regeneration, and peri-implant health restoration.